A petal-shaped MOF assembled with a gold nanocage and urate oxidase used as an artificial enzyme nanohybrid for tandem catalysis and dual-channel biosensing. Issue 30 (21st July 2021) - Sun, Zejun; Sun, Yujiao; Yang, Meng; Jin, Hui; Gui, Rijun
Abstract : A petal-shaped MOF assembled with a gold nanocage and urate oxidase used for tandem catalysis and dual-channel biosensing of uric acid. Abstract : A facile one-pot precipitation method was employed to prepare a petal-shaped hybrid under mild conditions. The hybrid is composed of urate oxidase (UOx) encapsulated into a zeolite-like metal–organic framework (MOF) with the doping of a hollow gold nanocage (AuNC). As one of the MOF–enzyme composites, a UOx@MOF(AuNC) hybrid with the features of artificial nanoenzymes was developed as a novel dual-channel biosensing platform for fluorescence (FL) and electrochemical detection of uric acid (UA). As for FL biosensing, enzymatic catalysis of the hybrid in the presence of UA triggered tandem catalysis and oxidation reactions to cause FL quenching. UA was linearly detected in the 0.1–10 μM and 10–300 μM ranges, with the limit of detection (LOD) of 20 nM. As for electrochemical biosensing, the hybrid was dropped on a glassy carbon electrode (GCE) surface to construct a hybrid/GCE platform. Based on the redox reaction of UA on the platform surface, UA was linearly detected in the 0.05–55 μM range, with a LOD of 15 nM. Experimental results confirmed that the hybrid-based dual-channel biosensing platform enabled selective and sensitive responses to UA over potential interferents. The platform has an excellent detection capability in physiological samples. The dual-channel biosensing platform facilitates the exploration of new bioanalysis techniques for early clinical diagnosis of diseases.